2011
DOI: 10.1016/j.jjcc.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in coronary angioscopy

Abstract: Angioscopy enables macroscopic pathological diagnosis of cardiovascular diseases from the inside. This imaging modality has been intensively directed to characterizing vulnerable coronary plaques. Scoring of plaque color was developed, and based on prospective studies; dark yellow or glistening yellow plaques were proposed as vulnerable ones. Colorimetry apparatus was developed to assess the yellow color of the plaques quantitatively. The effects of lipid-lowering therapies on coronary plaques were confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…To address these issues, direct endoluminal optical visualization or angioscopy has been proposed as an adjuvant imaging modality since the 1980s1 and has been used to visualize the human aorta,2,3 coronary4 and peripheral5 arteries, as well as therapies such as carotid6 and coronary7 angioplasty. Angioscopy has also been used to observe the placement of intravascular occlusion coils and stents in the carotid arteries of porcine and canine animal models,8 as well as to assess the completeness of clip occlusion in a canine aneurysm model 9.…”
mentioning
confidence: 99%
“…To address these issues, direct endoluminal optical visualization or angioscopy has been proposed as an adjuvant imaging modality since the 1980s1 and has been used to visualize the human aorta,2,3 coronary4 and peripheral5 arteries, as well as therapies such as carotid6 and coronary7 angioplasty. Angioscopy has also been used to observe the placement of intravascular occlusion coils and stents in the carotid arteries of porcine and canine animal models,8 as well as to assess the completeness of clip occlusion in a canine aneurysm model 9.…”
mentioning
confidence: 99%
“…There are only a few reports of human pathologic specimens of CTO in the literature. 1 Angioscopy has been reported to be useful for the direct visualization of thrombus and allows for characterization of the vessel wall from inside, 2 but we cannot observe the distal side of CTO in coronary arteries. Here we report an evaluation of the distal side of CTO of the superficial femoral artery (SFA) via a retrograde approach with angioscopy.…”
mentioning
confidence: 81%
“…Plaque color is classified as white, light yellow, yellow (medium yellow) or intensive yellow (dark yellow) 4,5) (Fig. 1A).…”
Section: Coronary Angioscopymentioning
confidence: 99%
“…Moreover it provides the detail information of plaque morphology or thrombus formation. 3,4) A lot of previous studies have shown that coronary angioscopy enabled not only the detection of vulnerable plaque but also prediction of cardiovascular events and percutaneous coronary intervention related complications.…”
Section: Introductionmentioning
confidence: 99%